First record of the snail-killing fly genus Dichetophora Rondani (Diptera: Sciomyzidae) in Korea, with descriptions of two new species - Son, Yeongjin; Suh, Sang Jae (Zootaxa, 2021)
This paper provides the first report of the snail-killing fly genus Dichetophora Rondani, 1868 on the Korean peninsula with the discovery of two new species, D. koreana sp. nov. and D. nigricorpa sp. nov. Descriptions and illustrations of the new species and keys to the Palearctic species of this genus are given.